The olive (Olea europaea) and the almond (Prunus amygdalus) related phytonutrients, and the associated health-promoting biological effects, a review - Alaya, Amina; Máthé, Anna Beáta; Frecska, Ede; Máthé, Endre (Acta Agraria Debreceniensis, 2021)
With the increasing attention to the health promoting activities of the bioactive compounds from some plants, many researchers are focusing on the biological potential and mechanisms of certain cultivated plant species. In this review, we survey the olive and almond based extracts specific phytoconstituents and their associated health promoting effects that have been evaluated in experimental and clinical studies.